Is This Distance Teaching Planning That Bad? - Mironowicz, Izabela; Schretzenmayr, Martina (Taylor & Francis, 2020)
In spring 2020, university courses were moved into the virtual space due to the Covid-19 lockdown. In this paper, we use experience from courses at Gdańsk University of Technology and ETH Zurich to identify core problems in distance teaching planning and to discuss what to do and what not to do in teaching planning after the pandemic. We conclude that we will not return to the state of (teaching) affairs that we had previously. The availability of recordings of lectures and videos, de-localisation of both students and teachers, the experience of spatio-temporal autonomy will lead to new forms of teaching as both students and teachers experienced some aspects of remote teaching even more efficient than real-world teaching. On the other hand, remote teaching of elements of learning that required interaction, e.g. group and studio work, brainstorming, discussion to foster critical thinking, cannot replace the real experience of the classroom.
Keywords: Hochschulstudium; E-Learning; Unterricht; Student; Hochschullehrer; Prüfung; Verhaltensänderung; Empirische Untersuchung; Erfahrungsbericht; Corona-Krise